STAFFING OIL AND GAS COMPLEX OF UKRAINE - Мандрик, Я. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article examines the history of the origin and development of schools of training oil and gas complex of Ukraine. Scientific analysis of training craftsmanship completes the formation of Ivano-Frankivsk branch of the Lviv Polytechnic. Also studied the formation and activities of these years, other educational institutions to prepare specialties of oil and gas from the secondary special education.